Calibration of thermal infrared channels of Feng Yun satellite data - Wan Kadir, Wan Hazli; Rasib, Abd. Wahid; Ibrahim, Ab. Latif; Zaini, Zawatil Azhani (2007)
Most of the obtained satellite data cannot get away from radiometric errors resulted from the effect of the atmosphere and sensor alignment movement. Therefore, post-launch calibration is one of the requirements to rectify all errors to ensure high accuracy of earth’s geophysical or biophysical information in the satellite data. The calibrated satellite data will represent the significant absolute values of ground features signal. In the present study, Feng Yun 1D (FY-1D) one of the Chinese’s meteorological satellites will be calibrated to obtain sea surface temperature of the South China Sea. The calibration coefficient of gain and offset for FY-1D thermal infrared channels (10.3 – 11.3µm and 11.5 – 12.5µm) will be determined using the linear plot of brightness temperature and ground truth temperature. The split window technique will be employed to derive the values of sea surface temperature from FY-1D thermal infrared channels. Result from this study showed that the gain and offset for FY-1D thermal infrared channels was 3.4617 and 170.87, respectively. The analysis was carried out by comparison to the sea surface temperature values between ground truth data acquired from Malaysian Meteorological Department and FY-1D using z-test. The analysis showed that the value of gain and offset were significant at z = 0.1418 which is below than 1.96 at 95% confidence level. In addition, the difference value of average sea surface temperature between ground truth observation and FY-1D data is 0.34ºC.